UPAYA MENINGKATKAN KEMAMPUAN MENYUSUN PARAGRAF BAGI MAHASISWA PGSD DALAM MATA KULIAH PENINGKATAN KETERAMPILAN BAHASA INDONESIA MELALUI PENDEKATAN KONSTRUKTIVISTIK - Hardiman Tantiana Isnaningsih (Elementary School: Jurnal Pendidikan dan Pembelajaran ke-SD-an, 2015)
This study aims to improve the ability compose paragraphs in subjects Indonesian LanguageSkills Improvement with constructivist approach. Subjects of this study is that a student one semesterstudies at the Open University UPBJJ S1 PGSD Yogyakarta. The study lasted for two cycles of action,which each cycle includes three sub-activities such as planning the action, observation and reflection.While the method of collecting data through observation and documentation. Data were analyzedusing quantitative descriptive analysis performed while gradually drawing conclusions from analysisof student assignments. Menyyimpulkan research results (1) pelaksananaan learning Indonesianlanguage skills improvement, especially compose a paragraph through a constructivist approach canimprove the ability of students compose paragraphs, (2) the results of the evaluation in class E 6100%of the number of students increased learning achievement, especially the ability to composeparagraphs mean average, an increase of 34.1 (initial conditions the average value increased 97.8 62.9(3) results after the conclusion of researchers carried out the action on the class E 6 through aconstructivist approach to learning to write paragraphs, there is a very significant achievementincrease of the average conditions aal until cycle 1 increased to 10.5, while from cycle I to cycle II, theaverage rose to 24.4 from an initial condition ii increased 34.1 on subjects Indonesian SkillsUpgrading using descriptive analysis.